Perancangan Kontrol Pelacakan Lintasan untuk Robot Otonom Bergerak Beroda dengan Penggerak Diferensial - Stephen I.C. Gulo; Tua Tamba (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
Differential drive wheeled mobile robots (DDWMR) is a class of mobile robots which has been used in various applications due to its mobile abilities. One important issue in the development of DDWMR is regarding the design of control methods to ensure the DDWMR can move autonomously from initial to final poses. The main challenge in such an issue is the need to design a controller which respects the nonholonomic constraint of DDWMR movements. To address such a challenge, this paper proposes a control method which combines techniques in smooth reference trajectory generation and Lyapunov-based tracking control designs. In the proposed method, a reference trajectory that is represented as polynomial function is first generated to connect the initial and final poses based on some waypoints information between them. A feedback control law based on Lyapunov’s stability method is then design to help control the DDWMR in tracking the generated reference trajectory with minimum error. Numerical simulation results are given to illustrate the effectiveness of the proposed method,